"It Could Affect You as a Person, Character-Wise": Promoting Character Development and Preventing Sexual Violence at West Point. Issue 4 (2nd October 2017) - Arbeit, Miriam R.
Abstract: The United States Military Academy at West Point develops cadets into "leaders of character" who will become Army officers. This focus on character presents an opportunity for the prevention of sexual violence through an emphasis on military values. Using constructivist grounded theory, this study examined how cadets experience their own sexual selfhood and their future roles as Army officers in relation to their values. The findings identified ways in which cadets were (a) finding strength and vulnerability in sexual desire, (b) shaping sexual identity through humility or hubris, (c) applying and misapplying military ethics, and (d) being optimistic yet underprepared for officership. These findings illustrate both opportunities and risks in leveraging character development approaches for sexual violence prevention in adolescence and the transition to adulthood.